Maternal DNA lineages at the gate of Europe in the 10th century AD - Rusu, Ioana; Modi, Alessandra; Vai, Stefania; Pilli, Elena; Mircea, Cristina; Radu, Claudia; Urduzia, Claudia; Pinter, Zeno Karl; Bodolică, Vitalie; Dobrinescu, Cătălin; Hervella, Montserrat; Popescu, Octavian; et al. (PLOS ONE, 2018)
Given the paucity of archaeogenetic data available for medieval European populations in comparison to other historical periods, the genetic landscape of this age appears as a puzzle of dispersed, small, known pieces. In particular, Southeastern Europe has been scarcely investigated to date. In this paper, we report the study of mitochondrial DNA in 10th century AD human samples from Capidava necropolis, located in Dobruja (Southeastern Romania, Southeastern Europe). This geographical region is particularly interesting because of the extensive population flux following diverse migration routes, and the complex interactions between distinct population groups during the medieval period. We successfully amplified and typed the mitochondrial control region of 10 individuals. For five of them, we also reconstructed the complete mitochondrial genomes using hybridization-based DNA capture combined with Next Generation Sequencing. We have portrayed the genetic structure of the Capidava medieval population, represented by 10 individuals displaying 8 haplotypes (U5a1c2a, V1a, R0a2’3, H1, U3a, N9a9, H5e1a1, and H13a1a3). Remarkable for this site is the presence of both Central Asiatic (N9a) and common European mtDNA haplotypes, establishing Capidava as a point of convergence between East and West. The distribution of mtDNA lineages in the necropolis highlighted the existence of two groups of two individuals with close maternal relationships as they share the same haplotypes. We also sketch, using comparative statistical and population genetic analyses, the genetic relationships between the investigated dataset and other medieval and modern Eurasian populations.